Lung involvement in systemic connective tissue diseases - Plavec Goran; Tomić Ilija; Bihorac Sanela; Kovačević Gordana; Pavlica Ljiljana; Cvetković Gordana; Sikimić Stevan; Milić Rade (Vojnosanitetski Pregled)
Background/Aim. Systemic connective tissue diseases (SCTD) are chronic inflammatory autoimmune disorders of unknown cause that can involve different organs and systems. Their course and prognosis are different. All of them can, more or less, involve the respiratory system. The aim of this study was to find out the frequency of respiratory symptoms, lung function disorders, radiography and high-resolution computerized tomography (HRCT) abnormalities, and their correlation with the duration of the disease and the applied treatment. Methods. In 47 non-randomized consecutive patients standard chest radiography, HRCT, and lung function tests were done. Results. Hypoxemia was present in nine of the patients with respiratory symptoms (20%). In all of them chest radiography was normal. In five of these patients lung fibrosis was established using HRCT. Half of all the patients with SCTD had symptoms of lung involvement. Lung function tests disorders of various degrees were found in 40% of the patients. The outcome and the degree of lung function disorders were neither in correlation with the duration of SCTD nor with therapy used (p > 0.05 Spearmans Ro). Conclusion. Pulmonary fibrosis occurs in about 10% of the patients with SCTD, and possibly not due to the applied treatment regimens. Hypoxemia could be a sing of existing pulmonary fibrosis in the absence of disorders on standard chest radiography.